Factors Influencing Decision Making to Adopt Cross-Border E-commerce - Andy Chia; Isnaini Nuzula Agustin (Penerbit Goodwood, 2026)
Purpose: This study aims to identify and analyze the factors that influence the decision of MSMEs in Indonesia to adopt cross-border E-commerce. The main focus is on six variables that refer to the TOE framework: perceived benefit, perceived security, perceived cost, government support, organizational readiness, and organizational innovativeness. Methodology/approach: This study used a quantitative approach through an online questionnaire survey distributed to 440 MSME owners in Indonesia. Purposive sampling was applied with the criterion that respondents were familiar with or used digital platforms for learning. Data were analyzed using PLS-SEM through SMARTPLS to test variable relationships, supported by descriptive analysis via SPSS to outline the respondent characteristics. Results: The results show that government support, organizational readiness, and organizational innovativeness significantly influence MSMEs’ adoption of Cross-Border E-commerce, while perceived benefit, perceived security, and perceived cost do not. The study highlights that adoption is driven more by organizational and environmental factors than by technology-related perceptions. Conclusions: Indonesian MSMEs’ decision to adopt cross-border E-commerce is mainly determined by their organizational readiness, innovation capabilities, and government support. Strengthening internal capacity and improving government facilities and policies are key factors driving MSME digital transformation success. Limitations: This study is limited to variables within the TOE framework and uses cross-sectional data; therefore, the findings cannot yet describe changes in MSME behavior comprehensively or be generalized to other countries. Contributions: This study provides practical insights for the government, MSME players, and researchers to formulate strategies to accelerate the adoption of cross-border E-commerce in Indonesia.